The Importance of Entrepreneurial Interest on Islamic State University of North Sumatera’s Management Students - Sri Kartika Dewi; Zuhrinal M. Nawawi (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to determine how important the interest in entrepreneurship is for students majoring in management at the State Islamic University of North Sumatra. This study uses a descriptive qualitative research method that aims to make the reality easier to study and also uses a questionnaire. The results of this study indicate that the importance of an interest in entrepreneurship must be re-grown in a student. entrepreneurship can also make a person gain a better position in the eyes of society and be able to face challenges. Where support from the family environment and the surrounding community also greatly influences someone's interest in entrepreneurship, where this support can encourage someone to become an entrepreneur.